Thickness Measurement of Polystyrene Coating on QCM Sensor using Interferometvanry Principles. Issue 1 (June 2021) - Anggraeni, D; Sakti, S P
Abstract: Coating film thickness is one of many important aspects in the development of Quartz Crystal Microbalance (QCM) for chemical sensors and biosensors. The coating layer is utilized as a matrix layer for the bio-sensitive molecule or as a sensitive layer. Also, the coating thickness is an important physical parameter, which determines the sensitivity and stability of the QCM sensor. Commonly for the thin film or glassy film, the Sauerbrey equation was used to calculate the film thickness. However, the method is inaccurate for a rubbery film. In this study, a non-destructive method was developed to measure the thickness of a transparent layer deposited on QCM using the interferometry method. This interferometry method uses the principle of coherent light interference between the initial laser beam and the one that has passed through a transparent layer. In this work polystyrene film which is known as a glassy film was used. The results of this study show that the interferometry method can be used to measure the thickness of the polystyrene layer deposited on the QCM sensor, as a non-destructive measurement method. These results are validated by calculations from the Sauerbrey equation, in calculating the thickness of polystyrene-based on changes in the frequency of the QCM sensor, which is 0.421 micrometers.